The effect of smoking cessation on work disability risk: a longitudinal study analysing observational data as non-randomized nested pseudo-trials - Airaksinen J.; Ervasti J.; Pentti J.; Oksanen T.; Suominen S.; Vahtera J.; Virtanen M.; Kivimäki M. (OXFORD UNIV PRESS, 2022)
Background: Smoking increases disability risk, but the extent to which smoking cessation reduces the risk of work disability is unclear. We used non-randomized nested pseudo-trials to estimate the benefits of smoking cessation for preventing work disability.
Methods: We analysed longitudinal data on smoking status and work disability [long-term sickness absence (>= 90 days) or disability pension] from two independent prospective cohort studies-the Finnish Public Sector study (FPS) (n = 7393) and the Health and Social Support study (HeSSup) (n = 2701)-as 'nested pseudo-trials'. All the 10094 participants were smokers at Time 1 and free of long-term work disability at Time 2. We compared the work disability risk after Time 2 of the participants who smoked at Time 1 and Time 2 with that of those who quit smoking between these times.
Results: Of the participants in pseudo-trials, 2964 quit smoking between Times 1 and 2. During the mean follow-up of 4.8 to 8.6 years after Time 2, there were 2197 incident cases of work disability across the trials. Quitting smoking was associated with a reduced risk of any work disability [summary hazard ratio = 0.89, 95% confidence interval (CI) 0.81-0.98]. The hazard ratio for the association between quitting smoking and permanent disability pension (928 cases) was of similar magnitude, but less precisely estimated (0.91, 95% CI 0.81-1.02). Among the participants with high scores on the work disability risk score (top third), smoking cessation reduced the risk of disability pension by three percentage points. Among those with a low risk score (bottom third), smoking cessation reduced the risk by half a percentage point.
Conclusions: Our results suggest an approximately 10% hazard reduction of work disability as a result of quitting smoking.